Evaluasi Kinerja Limestone Crushing Plant Terhadap Target Produksi 108.000 Ton/Bulan Pada PT Indocement Tunggal Prakarsa Tbk Unit Palimanan-Cirebon - Novi Herlinda; Delita Ega Andini; Haslen Oktarianty (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2021)
This research was conducted to optimize limestone production within a maximum of 30 days. The method used in this research is the frequency distribution statistical method for increasing the time of resistance, The data required are unit resistance hours at the Crushing plant. Based on research and calculations in the field, it is known that the work efficiency of the limestone crushing plant 09 unit is low, 62.87% with a total production only 73.846 tons/month. After many refinement efforts, work efficiency of the limestone crushing plant 09 unit increased 17.31% to 80, 19%, to increase the production target, refinement efforts were made to increase effective working hours by minimizing time constraints, and working time management accordingly production targets were achieved, therefore target production increased from 2,275 tons / shift to 4,173 tons / shift and the final production of crushing plant 09 increased to 125,190 tons / month